EVALUATION OF THE IMPLEMENTATION OF THE SCHOOL LITERACY MOVEMENT (GLS) PROGRAM IN BANTUL REGENCY - Andreanus Pattikawa Lbn Toruan; Nur Hidayanto Pancoro Setyo Putro; Sudiyatno Sudiyatno; Widowati Pusporini; Jeffri Dian Andika (JURNAL NALAR PENDIDIKAN, 2025)
This study aims to evaluate the achievement and differences in the implementation of the School Literacy Movement (GLS) program in elementary schools in Bantul Regency. This evaluative research employed a mixed-methods approach, utilizing the CIPP evaluation model with a quantitative descriptive orientation. Data were collected through questionnaires and interviews, involving respondents consisting of teachers and elementary students from one public and one private elementary school, namely SD Muhammadiyah Bendo and SD Negeri Sutran. The results at SD Muhammadiyah Bendo indicate that 28.13% fall into the "Very Good" category, 12.5% into the "Good" category, 21.88% into the "Fair" category, 18.75% into the "Poor" category, and 18.75% into the "Very Poor" category. Meanwhile, at SD Negeri Sutran, 25% are in the "Very Good" category, 40.6% in the "Good" category, 18.75% in the "Medium" category, 9.4% in the "Low" category, and 6.25% in the "Very Low" category. Overall, the findings reveal a distributional difference in survey results that reflects varying degrees of program success between the two schools. Based on the data distribution and the number of students in the lower categories, SD Negeri Sutran demonstrates a more consistent and comprehensive implementation of the GLS program compared to SD Muhammadiyah Bendo